Adab Bergaul dalam Kitab Wasiatul Musthofa Karya Imam Abdul Wahab Asy-Sya’roni dan Relevansinya dengan Materi Akidah Akhlak Kelas IX MTs - Ayu Milkhatun Nisa; Muchotob Hamzah; Yusuf Amin Nugroho (Student Research Journal, 2024)
This study is titled "Manners of Social Interaction in the Book Wasiatul musthofa by Imam Abdul Wahab Asy-Sya’roni and Its Relevance to the Aqidah Akhlaq Subject for 9th Grade MTs Students." The objectives of this study are: 1) To determine the content of the book Wasiatul musthofa , 2) To identify the manners of social interaction in the book Wasiatul musthofa , and 3) To understand the relevance of the manners of social interaction in the book Wasiatul musthofa with the Aqidah Akhlaq subject for 9th grade MTs students. This research employs a qualitative approach with a library research method. Data collection techniques include documentation and online data searches. Primary data sources are obtained from the book Wasiatul musthofa and the Aqidah Akhlaq textbook for 9th grade MTs, while secondary data sources are derived from reference books, articles, and relevant journals. The data analysis technique used is content analysis to understand the text. The results of the study indicate that: 1) The content of the book Wasiatul musthofa can be categorized into three main discussions: Aqidah, which includes the oneness of Allah, obedience to Allah, and preserving the religion of Allah; Syariah, which encompasses the Prophet's advice on the manner of worship by a servant to his Lord; and Akhlaq, which includes advice on the development of noble character. 2) The manners of social interaction in the book Wasiatul musthofa include several hadiths about loving one's brother, speaking the truth, and the prohibition of lying. 3) The analysis of the relevance of the book Wasiatul musthofa with the Aqidah Akhlaq subject for 9th grade MTs shows that almost all aspects of social interaction manners in the book align with the subject matter taught. The researchers conclude that the book Wasiatul musthofa can be used as an alternative supplementary book for teachers to enrich information, especially in the field of Akhlaq.